Laparoscopic repair of peptic ulcer perforation:Our experience - Hari Damde; Arpan Mishra; Jitendra Shakya; Mahendra Gond; Vikesh Agarwal (International Journal of Medical Research and Review, 2015)
Aim: To assess the feasibility of laparoscopic repair of peptic ulcer perforation and toanalyse the complications related to laparoscopic repair of peptic ulcer perforation.Material and Method: This was a Prospective, Observational study done in Department of Surgery, N.S.C.B. Medical College, Jabalpur from October 2013 to October 2014. The aim of study is found outcome and complications of laparoscopic repair of peptic ulcer perforation.Observations: A total of 13 cases were included under study criteria which were repaired with laparoscopic technique. There was good success rate with this technique. Intraoperative difficulties like technical difficulties in stabilization of stomach for localization of ulcer and hemodynamic instability for which conversion to open done with a conversion rate of 3 cases out of 13. These difficulties were later rectified. There was postoperative complicationseen with appearance of bilateral mild pleural effusion in single case. There were no postoperative complication like surgical site Infection, wound dehiscence, leak or fistula and no mortality.Conclusion: We concluded that laparoscopic repair of peptic ulcer perforation is a good alternative for open with early to normal life, less hospital stay and no postoperative wound infections